Analisis Perbandingan Kinerja Koperasi Merah Putih dengan KUD di Era Orde Baru, Studi Kasus pada Aspek Ekonomi dan Sosial - Moh. Ja’far Sodiq Maksum; Roosmarrani Setiawati; M. Farid Nasrullohi (Lembaga Institute Development of Social Economic Cociety, 2026)
This article analyzes the comparative economic and social performance between Koperasi Merah Putih—a national program for community-based village cooperatives launched in 2025—and Koperasi Unit Desa (KUD), which developed during Indonesia’s New Order era. The study employs a case study approach with a qualitative-comparative method enriched by quantitative projections of economic performance, based on historical data from KUD and projected growth for Koperasi Merah Putih. The theoretical framework draws upon the Cooperative Institutional Theory (Law No. 17/2012), Community-Based Economic Development (CBED), Social Capital Theory (Putnam, 1993), and Institutional Transformation Theory (North, 1990). The findings reveal that Koperasi Merah Putih demonstrates a more adaptive institutional design, broader business diversification, and higher member participation compared to KUD. Economic performance projections indicate significant potential contributions to village economies through multiplier effects across various sectors. Social capital rooted in active participation emerges as a key success factor, while the main challenges involve strengthening management capacity, digitalization, and independent oversight. The study recommends modern management training, implementation of external audits, and longitudinal research to continuously evaluate economic and social impacts.